2005
DOI: 10.1007/s00221-005-0079-x
|View full text |Cite
|
Sign up to set email alerts
|

Sustained attention in traumatic brain injury (tbi) and healthy controls: enhanced sensitivity with dual-task load

Abstract: Poor sustained attention or alertness is a common consequence of traumatic brain injury (TBI) and has a considerable impact on the recovery and adjustment of TBI patients. Here, we describe the development of a sensitive laboratory task in healthy subjects (Experiment 1) and its enhanced sensitivity to sustained attention errors in TBI patients (Experiment 2). The task involves withholding a key press to an infrequent no-go target embedded within a predictable sequence of numbers (primary goal) and detecting g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 30 publications
5
57
0
Order By: Relevance
“…Furthermore, in a related study, a switch cost was observed on the dual-task version of the SART in which the dual-task element, rather than making a verbal response, was to respond with a different key press to a grey digit. In that study, the dual-task switch cost was equal for TBI participants and controls (Dockree et al, 2006). We therefore feel that although switch costs will exist in tasks with dual-task elements, these switch costs do not interfere with the primary aim of assessing emergent awareness.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Furthermore, in a related study, a switch cost was observed on the dual-task version of the SART in which the dual-task element, rather than making a verbal response, was to respond with a different key press to a grey digit. In that study, the dual-task switch cost was equal for TBI participants and controls (Dockree et al, 2006). We therefore feel that although switch costs will exist in tasks with dual-task elements, these switch costs do not interfere with the primary aim of assessing emergent awareness.…”
Section: Discussionmentioning
confidence: 75%
“…These included: National Adult Reading Test (NART) (Nelson, 1982;Nelson & Willison, 1991), Hospital Anxiety and Depression Scale (HADS) (Zigmond & Snaith, 1983), Frenchay Aphasia Screening Test (FAST) (Enderby et al, 1987), and Frontal Assessment Battery (FAB) (Dubois et al, 2000). (Robertson et al, 1996) and the Sustained Attention to Response Task (Robertson et al, 1997, Manly et al, 2003, Dockree et al, 2006. Participants undertook three tasks of sustained attention: the Fixed SART, Random SART and the DART.…”
Section: Screening Testsmentioning
confidence: 99%
“…In other words, unless a significant cognitive demand was placed on the subject that required more than typical cognitive effort, no differences could be determined. Similarly, Bernstein (2002) demonstrated that by increasing the complexity of a dual task involving auditory and visual discrimination and measuring evoked responses that those with a history of concussion but ostensibly no residual complaints could be differentiated from controls (Dockree et al, 2006a).…”
Section: Pathophysiology Of Concussionmentioning
confidence: 98%
“…While 20 further studies are needed to confirm this possibility, it is notable that failures of inhibitory control behaviors are integral features of many psychiatric disorders and the mechanism of an inhibitory control system in rats has been the subject of substantial study (see review by Eagle and Baunez, 2010). Furthermore, deficits in behavioral inhibition have been observed in patients following TBI (Dimoska-Di Marco, et al, 2011;Dockree, et al, 2006;O'Keeffe, et al, 2007).…”
Section: Discussionmentioning
confidence: 99%